ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBANGUNAN MANUSIA DI PROVINSI MALUKU UTARA, 2007-2012 - , ASRIL, Prof. Dr. Samsubar Saleh, M.Soc.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the factors that influence human development index. The subjects were eight Districts / Municipal in North Maluku province, during 2007-2012. The data used are secondary data including the Human Development Index, economic growth, government spending on health and education in the areas of government spending. Analysis tools used in the study is the analysis of panel data regression with fixed effect model estimation techniques. The results showed that the variables of economic growth a positif and significant effect on IPM (probability 0.0000). Variable government health spending have positive and significant impact on IPM (probability 0.0002). Variable government spending on education a significant positive effect on IPM (probability 0.0000). The coefficient of determination shown by the R-square of 0.984 indicates that the variation of the independent variables in the model that explains the variation in HDI achievement level in the province of North Maluku period 2007-2012 was 98.4 percent, while the remaining 1.60 percent is explained by other variables out of the model.